PRESENTATION AND OUTCOME OF GASTRO-INTESTINAL TUBERCULOSIS IN DHQ TEACHING HOSPITAL, DIKHAN, PAKISTAN - Akhtar Munir (Gomal Journal of Medical Sciences, 2018)
Background: Intestinal TB is the sixth most frequent site for extra pulmonary tuberculosis. The objective of the study was to determine the presentation and outcome of gastro-intestinal tuberculosis Material & Methods: This was a descriptive cross-sectional study conducted in the department of General surgery, Gomal Medical College, DIKhan from January 2016 to January 2017. All admitted patients with gastrointestinal tuberculosis were included in the study. Sample size was 71 cases selected through consecutive sampling technique. Demographic variables were gender, age and socio economic status. Research variables were source of patients, weight of the patients, presence of acute/ sub-acute intestinal obstruction / or peritonitis, mode of treatment, presence of family history, presence of concomitant pulmonary tuberculosis and final outcome of the patients. All variables being categorical except age were analyzed descriptively into count and percentages using SPSS Version 16 whereas mean and range were calculated regarding age. Results: The age of the patients ranged from 13 year to 68 year with mean of 27.3 years. Out of a total of 71 cases, 43.7% males and 56.3% were female with male to female ratio of 1:1.2. All of the patients in this study were from poor socio-economic class. Ninty three pecent cases underwent surgical procedure. Seventy three percent of the patients were under-weight while 25.1% were of normal weight. Eleven cases were managed conservatively. Outcome was good in 80% patients, while 20% patients had poor prognosis. Conclusion: Early diagnosis, and timely intervention and starting Anti Tuberculous Therapy (ATT) play a significant role in the final outcome of gastro-intestinal tuberculosis.